Gestión administrativa para la Escuela de Capacitación de Choferes Profesionales de San Miguel de Bolívar, provincia Bolívar, ciudad San Miguel, periodo 2025-2030 - Mancheno Arteaga, Shirley Alicia (2025)
Administrative management within an educational institution is essential for efficient operation, proper work organization, and the achievement of its objectives. Several weaknesses in this area were identified at the San Miguel de Bolívar Professional Driver Training School, such as the absence of an updated strategic plan, a lack of performance evaluation, unclear planning, and limited staff participation in administrative decisions. Faced with this situation, this study aimed to design an institutional strategic plan for the 2025-2030 period, which will improve the school's administrative management and strengthen its organizational capacity. The methodology used was descriptive, with a mixed approach, and included staff surveys, interviews with authorities, and documentary analysis. A SWOT analysis was also conducted to identify the internal and external factors influencing the institution's administration. As a result, a strategic plan was proposed consisting of four main objectives: improving institutional operations through evaluations and recognitions; optimizing administration with clear plans and training; fostering continuous improvement; and incorporate technologies into management and teaching. This plan includes specific activities, necessary resources, responsible parties, and an implementation schedule. The proposal seeks to be a practical and useful tool that contributes to modernizing management, strengthening teamwork, and ensuring quality educational services.